(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2024)
Physicians sometimes face difficulty identifying underlying diseases of some signs and symptoms created by individuals intentionally but without any apparent practical gain. This case report presents the clinical profile of a woman aged 22 years with a history of recurrent bleeding from the oral cavity since childhood, which has recently been worsened and now involves bleeding from the nose, eye, ear, and umbilicus. However, no physical or laboratory abnormalities could be identified. She had mental trauma in her childhood. After a comprehensive assessment that included a medical history, observation, physical examination, and psychiatric evaluation, she was diagnosed with Munchausen syndrome, which is a psychological condition where people pretend to be ill or deliberately produce symptoms of illness in themselves. She was treated with pharmacotherapy and psychotherapy and discharged from the hospital bleeding-free, which persisted till several follow-up visits.